descompuneti x^2+9y^2-12xy+2x-6y
Răspunsuri la întrebare
Răspuns de
3
x^2+9y^2 - 12xy + 2x - 6y =
x² + 9y² - 6xy - 6xy + 2( x - 3y )=
( x - 3y )² + 2( x - 3y ) - 6xy =
( x - 3y )( x - 3y + 2) - 6xy
x² + 9y² - 6xy - 6xy + 2( x - 3y )=
( x - 3y )² + 2( x - 3y ) - 6xy =
( x - 3y )( x - 3y + 2) - 6xy
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă